Depresi, Paparan Media, dan Pengaruh Teman Sebaya dalam Perilaku Fad Diets Pada Remaja Putri di SMA Negeri 6 Yogyakarta - CHAERANI, HURIN RAFIQA; Kandarina, BJ Istiti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: According to adolescent, physical attraction is important because it will affect their social life and acceptance in the society. Therefore, in recent years, many adolescent girls performed fad diets as efforts of weight-loss so they can be accepted by both the social life and the society. Objectives: Find out the relationship between depression, media exposure and peer influence in fad diets behaviour in adolescent girls at SMA 6 Yogyakarta. Methods: The method used in this research was an observational cross-sectional design. Using the measuring tool in the form of a questionnaire that has been validated and has a reliability value > 0.6. Respondents in this research were 284 people with 75 people convicted of fad diets. Result: From this research, we found that there is no significant relationship between depression and media exposure with fad diets behavior with p-values on depression is 0.312 and p-value on media exposure is 0.243 But there is a significant relationship between peer influence and fad diets behavior with p-value on peer influence is 0.001. Conclusion: In this study, factor that affecting adolescent girls to perform fad diets was peer influence